Phylogenetic analysis of Indian isolates of Pasteurella multocida based on partial 16S rRNA gene sequences: Association of caprine isolate with lineage B - MISHRA, MADHU; SUMITHRA, T G; KUMAR, SANTOSH; GUPTA, SANTOSH KUMAR; AGARWAL, RAJESH KUMAR; NAGALEEKAR, VISWAS KONASAGARA (The Indian Journal of Animal Sciences, 2018)
Pasteurella multocida is responsible for diseases, which are endemic and economically important in India, still comparative investigations on phylogenetic relations of Indian P. multocida isolates are scarce. Therefore, present study was undertaken to understand the phylogenetic relationship of several isolates belonging to different host, place of isolation and capsular types based on partial 16S rRNA gene sequencing. In the current study, a 838 bp fragment of 16S rRNA gene of 35 field isolates of P. multocida belonging to different capsular types, recovered from cattle, buffalo, sheep, goat, pigs and birds, collected from different states of India sequenced and analyzed. There were 12 unique 16S rRNA types among 35 isolates, which clustered into 2 distinct phylogenetic lineages, viz. A and B. There were strong correlations between the phylogenetic relations and capsular types, with maximum heterogeneity seen among isolates of capsular type A. However, there was no clustering based on the host or place of isolation indicating the potential hazard of interspecies sharing and the possibility of translocation of infected animals across international borders. Moreover, one of the caprine isolates belonged to lineage B. To the best of our knowledge, this is the first report of a caprine isolate in lineage B, since lineage B is reported to be exclusively associated with birds and cats. It may be alarming that the strains of lineage B are becoming adapted to different host species.